γδ T Cell‐mediated Tumor Immunity is Tightly Regulated by STING and TGF‐β Signaling Pathways - Jing Luo; Shengli Wang; Quanli Yang; Qianqian Fu; Chuyun Zhu; Tao Li; Shuxian Yang; Yin Zhao; Rong Guo; Xiaosong Ben; Yuzhen Zheng; Sitao Li; et al. (Advanced Science)
Abstract The STING pathway plays a critical role in tumor immunosurveillance. However, the precise mechanisms by which STING regulates gamma delta (γδ) T cell function during tumor progression remain unclear. Herein, we find that tumor‐derived cyclic GMP‐AMP (cGAMP) activates a distinct STING pathway by inducing TBK1‐mediated phosphorylation of Eomes in γδ T cells during the early stage of tumor development is demonstrated. This activation leads to interferon‐gamma (IFN‐γ) production and consequent tumor surveillance. However, at advanced stages of tumor progression, the accumulation of immune‐suppressive cytokine transforming growth factor‐beta (TGF‐β) downregulates STING levels, compromising the function of γδ T cells. Notably, the synergism between TGF‐β inhibition and STING agonists effectively counteracts the immunosuppressive tumor microenvironment, thereby augmenting the antitumoral effects of γδ T cells. These findings present a novel mechanism involving STING‐mediated IFN‐γ production in γδ T cells and hold significant implications for the development of potent immunotherapeutic approaches against cancer.